Reviews and Interviews / Contributors - Ravvin, Norman; Simon, Sherry; Majer, Krzysztof; Fruzińska, Justyna; Salska, Agnieszka; Maszewska, Jadwiga; Maszewski, Zbigniew (Text Matters: A Journal of Literature, Theory and Culture, 2015)
Norman Ravvin: A goldene medine? A Dialogue in Many Voices on Canadian Jewish Studies and Poland This paper is an account of the conference titled Kanade, di goldene medine? Perspectives on Canadian-Jewish Literature and Culture / Perspectives sur la littérature et la culture juives canadiennes, which took place in Łódź in April, 2014 as a result of collaboration between the University of Łódź and Concordia University (Montreal). As a venue for discussing Canadian Jewish identity and its links with Poland, the conference supported a dialogue between Canadians, Polish Canadianists, and European scholars from further afield. Established and young scholars attended from Germany, the United Kingdom, France, Belgium, the Czech Republic, and Canada, in addition to many Polish participants. The presence of scholars such as Goldie Morgentaler or Sherry Simon as well as curator Barbara Kirshenblatt-Gimblett contributed to an examination of both past and present Canadian and Polish Jewish life and led to an examination of Polish and Canadian literature and history from a highly personal perspective. Conference-goers took advantage of the opportunity to get to know Łódź, via walking tours and a visit to the Łódź Jewish community’s Lauder-funded centre on Narutowicza. The paper aims, as well, to investigate how the history of Jewish Łódź is conveyed in the novels of Joseph Roth and Chava Rosenfarb. The Task of Attention. Sherry Simon (Concordia University) Talks to Krzysztof Majer and Justyna Fruzińska (University of Łódź) American Studies in Poland: A Collective Enterprise. An Interview with Agnieszka Salska by Jadwiga Maszewska and Zbigniew Maszewski (University of Łódź)